Pengetahuan Kader Tentang Faktor Risiko Preeklampsia - Siti Sopiatun; Desy Rizki Ariani; Rifka Alindawati (Indonesian Health Issue, 2025)
Background Preeclampsia is the leading cause of maternal death in Indonesia at 37.1%. Preeclampsia is prevalent in 50 health center work areas in Karawang Regency. The number of preeclampsia cases is 17.52% of 8285 high-risk pregnant women. Failure to identify and manage cases based on risk factors also contributes to maternal death due to preeclampsia. The objective of this study is to enhance cadres' understanding of preeclampsia by enhancing their capacity to identify risk factors for preeclampsia at the Kertamukti Health Center. Aim: This study aims to explore the knowledge of cadres about the risk factors for preeclampsia. Method: This study uses a qualitative approach by conducting FGD (Focus Group Discussion). There were two discussion groups, each consisting of 12 cadres. Purposive Sampling Technique. The informants are Posyandu cadres and have been categorized in the FGD group. The analysis uses an analysis theme by creating keywords and matrices.  Result: Cadres do not know other names for preeclampsia and are still unfamiliar with the term. Cadres only know the term high blood pressure. so they do not understand the risk factors for preeclampsia. Conclusion: The study focuses on two major themes: the knowledge of preeclampsia and the collaboration between midwives and cadres. The term preeclampsia is still widely unknown and not understood by cadres.